2017
DOI: 10.1093/mnras/stx1747
|View full text |Cite
|
Sign up to set email alerts
|

Observational consequences of optical band milliarcsec-scale structure in active galactic nuclei discovered by Gaia

Abstract: We interpret the recent discovery of a preferable VLBI/Gaia offset direction for radioloud active galactic nuclei (AGNs) along the parsec-scale radio jets as a manifestation of their optical structure on scales of 1 to 100 milliarcseconds. The extended jet structure affects the Gaia position stronger than the VLBI position due to the difference in observing techniques. Gaia detects total power while VLBI measures the correlated quantity, visibility, and therefore, sensitive to compact structures. The synergy o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 61 publications
6
32
2
Order By: Relevance
“…The height of the peak with respect to the background is 2.8 versus 1.7 and the full width at half maximum (FWHM) is 0.42 rad versus 0.62 rad. We confirmed that anisotropy of ψ angle is not an artifact of Gaia DR1, and the prediction made in Petrov & Kovalev (2017b) has come true.…”
Section: Analysis Of Vlbi/gaia Position Angles With Respect To the Jesupporting
confidence: 79%
See 1 more Smart Citation
“…The height of the peak with respect to the background is 2.8 versus 1.7 and the full width at half maximum (FWHM) is 0.42 rad versus 0.62 rad. We confirmed that anisotropy of ψ angle is not an artifact of Gaia DR1, and the prediction made in Petrov & Kovalev (2017b) has come true.…”
Section: Analysis Of Vlbi/gaia Position Angles With Respect To the Jesupporting
confidence: 79%
“…Brightening a jet component shifts the centroid temporarily and irregularly. We call this behavior jitter and we predicted it in Petrov & Kovalev (2017b). Unlike to proper motions of stars, extending the observation interval does not result in a convergence of a proper motion estimate to some value with small uncertainty.…”
Section: Analysis Of Gaia and Vlbi Proper Motionsmentioning
confidence: 81%
“…They also found that in 80% of Seyfert 2 galaxies, the associated Gaia position related to the jet is located farther away from the nucleus than the VLBI core. This offset could be explained by the presence of a bright extended optical jet which shifts the Gaia centroid [40,41]. While this interpretation might seem appealing in view of the extended lobe structure reported by Lal & Ho [11], in our VLBI data, we do not find any supporting evidence for large scale-jets, which makes this interpretation less likely.…”
Section: Vlbi Structure Of the Target Sourcescontrasting
confidence: 76%
“…The smaller the viewing angle of a jet, the stronger is the Doppler boosting of the source emission leading to a "favoritism" in the observed properties of a flux limited AGN sample. Recent high-resolution observations of the jets in M 87 and 1H 0323+342 indicate the collimation and acceleration of the jets on scales up to hundreds of parsecs (Asada & Nakamura 2012, Hada et al 2017, Petrov & Kovalev 2017b.…”
Section: Introductionmentioning
confidence: 97%